2022
DOI: 10.3390/s22072677
|View full text |Cite
|
Sign up to set email alerts
|

Improving Prediction Accuracy and Extraction Precision of Frequency Shift from Low-SNR Brillouin Gain Spectra in Distributed Structural Health Monitoring

Abstract: In this paper, we studied the possibility of increasing the Brillouin frequency shift (BFS) detection accuracy in distributed fibre-optic sensors by the separate and joint use of different algorithms for finding the spectral maximum: Lorentzian curve fitting (LCF, including the Levenberg–Marquardt (LM) method), the backward correlation technique (BWC) and a machine learning algorithm, the generalized linear model (GLM). The study was carried out on real spectra subjected to the subsequent addition of extreme d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 53 publications
(57 reference statements)
0
8
0
Order By: Relevance
“…Nordin et al [151][152][153] proposed the use of GLM to extract temperature. GLM is a generalized form of linear regression that does not assume that the response variables (targets) are normally distributed.…”
Section: Machine Learning For Temperature and Strain Predictions Dire...mentioning
confidence: 99%
See 1 more Smart Citation
“…Nordin et al [151][152][153] proposed the use of GLM to extract temperature. GLM is a generalized form of linear regression that does not assume that the response variables (targets) are normally distributed.…”
Section: Machine Learning For Temperature and Strain Predictions Dire...mentioning
confidence: 99%
“…Specifically, the temperature extraction time was approximately two orders of magnitude faster than the LCF, while the temperature error improvement varied from approximately 0.4 • C to 5 • C, depending on the frequency-tuning step and the temperature conditions. The authors in [151] concluded that GLM in combination with conventional BFS extraction methods, such as LCF, results in a significant increase in temperature accuracy even when the SNR is low. The most important characteristic of the GLM is the easy interpretation, which arises from the algorithm's simplicity and its straightforward implementation.…”
Section: Machine Learning For Temperature and Strain Predictions Dire...mentioning
confidence: 99%
“…The correlation peaks were interpreted as events, and only after that, the variational mode decomposition technique was applied to classify different impacts on the sensor. The mentioned study [38] showed that the raw signal of a distributed fiber optic sensor is quite difficult to use for decomposition or for machine learning, so it still requires pre-processing: for example, by Wavelet and Curvelet filtering or/and correlation algorithms [39][40][41][42]. Primary processing of raw data should be implemented on simple mathematical operations, since the volume of processed data is quite high, and the algorithms themselves are implemented with the use of programmable microcontrollers.…”
Section: Introductionmentioning
confidence: 99%
“…There are also papers devoted to the use of various methods in conjunction with each other. Thus, in [23], the positive and negative aspects of the joint use of correlation methods and artificial intelligence are evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…Determining the optimal shift F, at which the convolution maximum was reached, the authors found the position of the maximum of the Brillouin spectrum as fC + F/2, where fC is the center frequency in the scanning range (Figure 1). Theoretically, the dependence of the original and shifted Lorentzian function's convolution value on the value of the shift between them is also a Lorentzian function with twice Fibers 2023, 11, 51 3 of 13 the half-width at half-height (for a derivation, see, for example, [23]). Additionally, since the role of the noise terms decreases when convolution is taken due to statistical averaging, this resulting Lorentzian function (hereinafter referred to as the correlogram) should have a greater SNR than the original BGS.…”
Section: Introductionmentioning
confidence: 99%